The Impact of Development and Training, Work Life Quality, Self Efficacy, Safety, and Job Satisfaction On Employee Performance - Abdulmalek Ali; Naelati Tubastuvi; Suryo Budi Santoso; Eko Hariyanto (International Journal of Management Science and Information Technology, 2024)
This research delves into five pivotal factors influencing employee performance within business contexts. This study examines the effects of development and training, work-life quality, self-efficacy, safety, and job satisfaction on employee performance. This article seeks to acquire insights into the mechanisms that determine performance results by investigating the correlations between these parameters. For this purpose, data was collected from 135 employees, a total of 360 employees of Al-Saeed Company, one of the most prominent Yemeni companies in the contracting and construction field in Yemen, through the questionnaire and analyzed the data using the PLS software. Findings confirm that development and training, work-life quality, safety, and job satisfaction do not affect employee performance, while self-efficacy positively influences employee performance.